Assess Water Usage Behavior and Calculate Personal Water Footprint of Lang Son Province Residents - Thi Thu Ha, Pham; Dinh Anh, Nguyen; Thi Viet Anh, Pham; Minh Loan, Luu (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2S, 2025)
This study aims to assess water usage behavior and calculate the personal water footprint (WF) of residents in Lang Son province. A self-administered survey of water users was conducted for citizens in four wards from February to March 2025. The research develops a questionnaire to calculate personal WFs for Lang Son province using a cross-sectional approach. The results show that the average WF was 6030.41 liters per capita per day (LPCD), of which the direct WF was 464.32 LPCD and the virtual WF was 5566.10 LPCD. The daily water usage behavior of the residents is less than optimal. The study also indicates a significant average difference in WFs among different age groups and living areas. Based on these findings, the research provides recommendations and solutions to raise community awareness about the importance of water conservation, encourage a shift toward sustainable water usage behaviors, and propose effective water resource management policies.